Study of Effect of Diesel Fuel Energy Rate in Duel Fuel on Performance of Compression Ignition Engine - Maan Janan Basheer (Al-Khwarizmi College of Engineering – University of Baghdad, 2012)
The aim of this work is to study the effect of diesel fuel percentage on the combustion processes in compression ignition engine using dual fuel (diesel and LPG). The brake thermal efficiency increased with the increase of diesel fuel rate at low loads, and decreased when load increased. To get sufficient operation in engine fueled with dual fuel, it required sufficient flow rate of diesel fuel, if the engine fueled with insufficient diesel fuel erratic operation with miss fire cycles presented.Dual-fuel operation at part load showed higher specific fuel consumption than straight diesl operation. At full loads, brake specific fuel consumption of duel fuel engine approaches that for diesel fuel values.